Valorization of Chemical Wastes: Ir(biscarbene)-Catalyzed Transfer Hydrogenation of Inorganic Carbonates Using Glycerol - Cheong, Yeon Joo; Sung, Kihyuk; Park, Sehoon; Jung, Jaehoon; Jang, Hye Young (ACS Sustainable Chemistry and Engineering, 2020)
Ir(biscarbene)-catalyzed transfer hydrogenation of sustainable and practical C1 sources (inorganic carbonates: K2CO3, KHCO3, Na2CO3, NaHCO3) with a green hydrogen source, glycerol, was conducted to afford formates and lactates with high turnover numbers (TONs) and turnover frequencies (TOFs) (formates (TON 16856 and TOF 843 h-1) and lactates (TON 32609 and TOF 1630 h-1)). Ir catalysts possessing various biscarbene ligands were employed, and the structural effects of Ir(biscarbene) catalysts were reflected on the catalytic activity. The CO2 reduction activity of Ir(biscarbene) catalysts is strongly dependent on the structure of biscarbene ligand, i.e., the length of the alkyl chain between two carbene groups and the wing-tip substituent of carbenes, of which the detailed reaction mechanism composed of β-hydride elimination of glycerol and CO2 reduction and different binding energies of CO2 with catalysts involving propylene- and methylene-linker-containing biscarbenes were elucidated by density functional theory calculations.
Keywords: Bis-carbene ligands; Detailed reaction mechanisms; Hydride elimination; Hydrogen sources; Structural effect; Transfer hydrogenations; Turnover frequency; Turnover number; Carbonates; Formate; Glycerol; Iridium; Lactate; Transfer hydrogenation